“Pluck These Bastards Feather by Feather Out of Their Rigid Thought…” On the Correspondence Between Jerzy Giedroyc and Melchior Wańkowicz (1945–1963) - Saignes, Anna (Porównania, 2025)
The article attempts to reconstruct the relationship between two important witnesses of the 20th century: the writer Melchior Wańkowicz and the editor of the monthly “Kultura” (Culture), Jerzy Giedroyc. The research material is primarily their published correspondence from 1945–1963. The article highlights the maturation of two concepts of freedom which, starting from a common basis, are becoming increasingly antinomic: Giedroyc’s concept dictates staying away from Poland and a strong commitment to the United States’s side; Wańkowicz’s concept implies a return to Poland, a choice resembling acceptance of enslavement, yet reflecting a different understanding of the struggle for freedom, consisting above all in avoiding any ideological consolidation.